2019
DOI: 10.31878/ijcbr.2019.53.5
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from performance of students of Pharmacology in self coded surprise test with negative marking.

Abstract: Introduction: The present study aims to find the effect of instruction of negative marking in a self-coded MCQ examination on the performance of students in the subject of Pharmacology with respect to the raw score, correct score and negative score. Material and methods: This longitudinal study was conducted in the Department of Pharmacology, Rural Medical College, Loni. The Second MBBS students were exposed to a self-coded MCQ test twice by surprise. The first test (T1) was given without instructions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The Raw score, Negative score and Corrected score along with Difficulty and Discrimination index of each MCQ was calculated. The students used their own alphanumerical code as described by Narwane et al 4 All the coded papers were assessed by a teacher unaware of the identity of students and the purpose of this educational study. After the completion of assessment, difficulty and discrimination index during T1 and T2 for each MCQ were calculated using Raw score, Corrected score and Negative score.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Raw score, Negative score and Corrected score along with Difficulty and Discrimination index of each MCQ was calculated. The students used their own alphanumerical code as described by Narwane et al 4 All the coded papers were assessed by a teacher unaware of the identity of students and the purpose of this educational study. After the completion of assessment, difficulty and discrimination index during T1 and T2 for each MCQ were calculated using Raw score, Corrected score and Negative score.…”
Section: Methodsmentioning
confidence: 99%
“…The indices, namely difficulty Discrimination indices are the important tools of item analysis. 3 In a study by Narwane et al, 4 it was observed that there was a negative impact on the performance of students, when the instructions of negative marking were given. Therefore it is also likely that the parameters of item analysis would also be affected.…”
Section: Introductionmentioning
confidence: 99%